2008
DOI: 10.1103/physrevstab.11.041002
|View full text |Cite
|
Sign up to set email alerts
|

Electron cloud observations and cures in the Relativistic Heavy Ion Collider

Abstract: Since 2001, the Relativistic Heavy Ion Collider has experienced electron cloud effects, some of which have limited the beam intensity. These include dynamic pressure rises (including pressure instabilities), tune shifts, a reduction of the instability threshold for bunches crossing the transition energy, and possibly incoherent emittance growth. We summarize the main observations in operation and dedicated experiments as well as countermeasures including baking, nonevaporable getter coated warm beam pipes, sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…The results of measurements reported in the literature show that energy of electrons impinging on the beam chamber is not greater than 600 eV in the LHC [26] and SPS [27], and not greater than 500 eV in RHIC [18]. The material parameters influencing the SEY are the penetration depth of the primary electron, the stopping power, the escape depth of the secondary electrons, the atomic number Z and, to a lesser extent, the work function [28].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The results of measurements reported in the literature show that energy of electrons impinging on the beam chamber is not greater than 600 eV in the LHC [26] and SPS [27], and not greater than 500 eV in RHIC [18]. The material parameters influencing the SEY are the penetration depth of the primary electron, the stopping power, the escape depth of the secondary electrons, the atomic number Z and, to a lesser extent, the work function [28].…”
Section: Discussionmentioning
confidence: 79%
“…making grooves) [3,16]; (c) Coating with low SEY materials (such as TiN [17], NEG [18] and amorphous carbon (a-C) [19]); (d) Coating with low SEY microstructure (ex. : copper black, gold black; columnar NEG) [20,21,22]; (f) Various combinations of above.…”
Section: Introductionmentioning
confidence: 99%
“…11 and 12, and Ref. [45]). The most limiting effect was seen at store, when electron clouds were formed in some of the experiments after the bunches are transferred from the accelerating to the storage RF system.…”
Section: Number Of Bunchesmentioning
confidence: 92%
“…11 the measured electron flux into the wall and pressure is shown as a function of the total filled proton intensity. An analysis of the dynamic pressure rises in RHIC concluded that all operationally relevant observation are caused by electron clouds [45].…”
Section: Beam Accumulationmentioning
confidence: 99%
See 1 more Smart Citation